Daun Zaitun dalam Pengobatan Sakit Gusi: Studi Takhrij dan Syarah Hadis - Dinar Siti Nur Aisyah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss about olive leaf as a medicine for sore gums. This study uses a qualitative type of method that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of this study indicate that the quality status of the hadith about olive leaf as a medicine for gum disease is considered authentic based on the takhrij hadith. And the hadith syarah shows that olive leaf is a medicine for gum pain which in olive leaf contains antimicrobials that are able to overcome infections that cause swollen gums and olive leaf is also analgesic so it is effective in relieving pain. This study concludes that the hadith about olives is acceptable (maqbul) so that it can be used as evidence for Islamic practice. This study recommends accessing information from the Prophet's hadith about olive leaf for the development of gum disease medicine in the medical world.